Romanian Conference on Medical Informatics : MEDINF'95 : Bucharest, 3-5 November 1995 : extended abstracts - Niculescu, Magdalena; Comşa, Liliana; Alexandru, Gabi; Neacşu, Lenuţa (Romanian Medical Informatics Society, 1995)
Extended abstracts of papers delivered at the Romanian Conference on Medical Informatics, MEDINF'95, in 1995.
Keywords: Medical Informatics Applications; mezinárodní spolupráce; lékařská informatika; Medical Informatics; Rumunsko; využití lékařské informatiky; International Cooperation; Romania